The Efficacy of Phototherapy in the Treatment of Neonatal Jaundice - Khalid Yas Khudhur (Institute of Medico-legal Publications Pvt Ltd, 2021)
Phototherapy is safe and effective in the management of neonatal hyperbilirubinemia; its efficacy has been demonstrated in several studies.A prospective study done on 100 cases of newborns with jaundice admitted to the pediatric ward at Tikrit Teaching Hospital during January to July 2009 were selected randomly, aim to evaluate the efficacy of phototherapy used in the treatment of significant indirect hyperbilirubinemia. The total serum bilirubin determinations were performed on newborns with jaundice. The current study demonstrated a statistically significant positive relation between the rate of TSB decrement and supplementary feeding, B.Wt. and type of light ,and a statistically non-significant negative relation between the rate of TSB decrement and gestational age, type of jaundice and receiving IVF. Conclusion: the efficacy of phototherapy in neonates with mixed feeding more than the bottle feeding and breast feeding, also the response to phototherapy in VLBW newborns was significantly slower than that of NBW and LBW. neonates under blue light phototherapy showed faster response than those under white light.